Fibroepithelial Polyp of the Buccal Mucosa: a case report (GAIMS Journal of Medical Sciences, 2023)
BackgroundFibroepithelial polyp is one of the benign lesions of oral cavity which occurs as inflammatory response to trauma. It is mostly asymptomatic but sometimes causes problems of mastication. Clinically, patients with fibroepithelial polyp present to the hospital as a painless pedunculated or sessile swelling. They can be treated by simple surgical excision or by other methods such as electrocautery or laser ablation.MethodsIn our case, a 62-year-old man reported to the ENT OPD with a soft to firm, painless pedunculated swelling in the right buccal mucosa which was surgically excised under local anesthesia.ResultsHistopathological examination of the excised specimen confirmed the diagnosis as fibroepithelial polyp.ConclusionFibroepithelial polyp should be kept as one of the differential diagnoses of benign soft tissue lesions of the oral cavity.